EVALUATION OF QUALITY OF MYCORRHIZAL MULBERRY LEAVES THROUGH SILKWORM REARING - SETUA, G.C.; KAR, R.; MAJI, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
The quality and quantity of mulberry leaves var. Si associated with three strains of Va mycorrhiza separately with graded levels of phosphorus (180, 90, 60, and 30 Kg P/ha/yr) were studied at CSR&TI, Berhampore (W.B.) for 2 years (1996-97 & 1997-98). Two years average data revealed the overall improvement in leaf yield, leaf moisture (%) and P uptake by leaves in all thė VAM-treated mulberry plants (Var. S1) particularly associated with Glomus mosseae_at 30Kg P/ha/yr which statistically found to be at par with control (180 Kg P/ha/yr without VAM) and other treatments. The silkworm rearing result with Multi x Bi (CB5 x P5) hybrid indicated the overall improvement in larval weight, single shell weight, S.R.%, absolute silk content in mycorrhizal leaves of any of the strains under reduced doses of P when fed to silkworms, while ERR, filament length, denier and non-breakable filament length were found to be at par with control. It was further observed that Glomus etunicatum with 50% reduced dose of P during favourable season and G. fasciculatum with 67% reduced dose of P during unfavourrable season performed better result in respect of important economic characters of rearing and reeling.